Anti-hyperglycemic and toxicological effects of a traditional polyherbal formulation, Athamathurot, used at Bantakhun hospital, Thailand - Acharaporn Issuriya; Palika Wetchakul; Surasak Limsuwan; Siriwimol Jiwpraditkul; Patcharawalai Jaisamut; Thammarat Kaewmanee; Jo Aan Goon; Sineenart Sanpinit (Journal of Agriculture and Food Research)
Objectives: Athamathurot decoction (Atha-D) has been used clinically for several years in the management of prediabetic individuals at Bantakhun hospital, Thailand, and has a long history of use as a formula for diabetes-related symptoms. However, the scientific information supporting its claim has never been described. This study aimed to investigate anti-diabetic properties and conduct the safety assessment of Atha-D. Methods: In acute toxicity, Atha-D was administrated at a dose of 2000 mg/kg p.o. in rats. Atha-D was given daily at doses of 50–500 mg/kg p.o. for 28 days to investigate its cumulative toxic effect. Histopathological features of internal organs and hematological and biochemical parameters were examined. Anti-diabetic properties were evaluated based on its in vitro anti-amylase and α-glucosidase activities as well as its hypoglycemic effect using the oral glucose tolerance test in overnight fasted normal rats. Results: The LD50 of Atha-D was estimated to be higher than 2000 mg/kg. Repeated dose toxicity for 28 days revealed that the no-observed-adverse-effect level (NOAEL) is 500 mg/kg, with a human equivalent dose (HED) of 80 mg/kg. The formulation exhibits notable anti-α-glucosidase activity with an IC50 value of 1.61 ± 0.05 μg/mL. In normoglycemic fasted rats, 500 mg/kg dose showed a hypoglycemic effect in glucose-loaded rats. Conclusions: Despite the promising anti-diabetic effect found in Atha-D, this herbal formulation does not create adverse effects in animals after acute and subacute treatment. Further pharmacological investigations, quantification of biological markers, and clinical studies are urgently required to support the utilization of this formulation in the management of prediabetic patients.